Discovery of multi‐megabase polymorphic inversions by chromosome conformation capture sequencing in large‐genome plant species. (28th November 2018) - Himmelbach, Axel; Ruban, Alevtina; Walde, Ines; Šimková, Hana; Doležel, Jaroslav; Hastie, Alex; Stein, Nils; Mascher, Martin
Summary: Chromosomal inversions occur in natural populations of many species, and may underlie reproductive isolation and local adaptation. Traditional methods of inversion discovery are labor‐intensive and lack sensitivity. Here, we report the use of three‐dimensional contact probabilities between genomic loci as assayed by chromosome‐conformation capture sequencing (Hi‐C) to detect multi‐megabase polymorphic inversions in four barley genotypes. Inversions are validated by fluorescence in situ hybridization and Bionano optical mapping. We propose Hi‐C as a generally applicable method for inversion discovery in natural populations. Significance Statement: This paper reports a method to detect megabase‐scale chromosomal inversions in plant species with large genomes through chromosome conformation capture sequencing.